Cattaneo–Christov intensity of magnetised upper-convected Maxwell nanofluid flow over an inclined stretching sheet: A generalised Fourier and Fick's perspective. (September 2017) - Acharya, Nilankush; Das, Kalidas; Kundu, Prabir Kumar
Highlights: Cattaneo-Christov effect on upper convected Maxwell nanofluid flow over inclined stretching sheet has been studied. More generalised version of so called Fourier and Fick law have been explored under the illumination of magnetic field. Leading equations have been cracked via RK-4 method in conjunction of shooting procedure. Thermal relaxation parameter aids the fluid's temperature to reduce significantly. Classical Fick's law contributes maximum concentration distribution only for δc . Abstract: The present study exemplifies the systematic analysis of the boundary layer Cattaneo-Christov model of heat and mass transport of the upper-convected Maxwell nanofluid passed by an inclined stretching surface in the presence of magnetic field. The pioneering step i.e. the upper-convected material derivative has been constructed to frame generalised Fourier's and Fick's phenomenon on behalf of the Cattaneo-Christov model. Governing non-linear PDEs are renovated to ODEs and then worked out via RK-4 procedure. Influences of flow factors inside flow regime, namely, fluid relaxation parameter δ m, thermal relaxation parameter δ e, nanoparticle concentration relaxation parameter δ c are deliberated through tables and graphs to predict the double diffusive phenomenon truthfully. Our investigation authenticates that higher temperature distribution profile is noticed for δ e  = 0.0 i.e. so called Fourier's law as compared to Cattaneo-Christov heat flux model. Thus the significance of the current literature is to explore its unique endeavour towards the generalised version of conventional Fourier's law and Fick's law at nanostructure level. Graphical abstract: Figure of the mathematical model.